A Universal Strategy for Organic Fluid Phosphorescence Materials. Issue 34 (16th July 2021) - Sun, Siyu; Wang, Jie; Ma, Liangwei; Ma, Xiang; Tian, He
Abstract: It is an accepted approach to construct room‐temperature phosphorescence (RTP) materials by suppressing the non‐radiative decay process. However, there is limited success in developing fluid phosphorescence materials owing to the ultrafast non‐radiation relaxation of vibration and collision of molecules in fluid matrixes. Here, a universal deep‐eutectic‐solvent strategy is proposed for developing pure organic phosphorescent fluid materials that are able to generate effective phosphorescent emissions at both room temperature (ΦRTP, 293 K ≈30 %) and even higher temperature (ΦRTP, 358 K ≈4.53 %). Based on these findings, a qualitative analytical method was developed for leak detection and a quantitative analytical technique was further validated to help visually identify the heat distribution of irregular surfaces. This advancement empowers the current organic phosphorescent system offering an alternative to determine moisture and heat from non‐invasive photoluminescence emission colors. Abstract : A general and effective strategy for the preparation of pure organic fluid materials with effective room‐temperature phosphorescence emission was proposed. The material was observed to have moderate phosphorescent emission even at 85 °C, based on which a temperature detection strategy was developed.